Les habits de l’identité maya yucatèque moderne - Gauthier, Mélissa (Material Culture Review, 2002)
In the Yucatan, the population is referred to as mestizo in reference to its regional clothing, or as catrine for its Western clothing. The description and analysis provided of how people dressed in different eras calls into question whether the nature of the influence of Western apparel in mestizo clothing systems is in fact always the same. The period of conquest, marked by missionaries’ obsession with clothing the naked bodies of "Mayan Indians" and by the use of clothing to reinforce the social order of the colony, led to the creation of the temo, a garment specific to the mestizos that is similar to the indigenous huipil, but distinct in its adornment. The adoption of the terno as the festive costume of the Yucatan in the 1840s by women dressed in the European style can be interpreted as a political strategy by the bourgeoisie, trying to show the Yucatan as a mestizo society. At the beginning of the twentieth century, this region of Mexico was inhabited by gentes de vestido dressed in the European style and by mestizos wearing mainly the distinctive Yucatan costume. Today, the variety ofhuipiles worn in rural areas reveals the coexistence of different cultures in Mayan communities. Résumé Au Yucatan, des habitants sont appelés mestizos en référence à leurs habits régionaux et d’autres, cabines d’après leurs vêtements occidentaux. Dans cet article, la description et l’analyse de certaines pratiques vestimentaires à différentes époques remettent en question le caractère immuable de la circulation des modes occidentales dans le système d’habillement mestizo. La période de la conquête, marquée par l’obsession des missionnaires de vêtir les corps dénudés des « Indiens mayas » et l’utilisation du vêtement pour renforcer la structure sociale de la colonie, a fait naître une tenue exclusive aux mestizas, le terno, semblable au huipil indigène mais distinct par l’ornementation. L’adoption du terno comme costume festif yucatèque dans les années 1840 par les femmes vêtues à l’européenne peut être interprétée comme une stratégie politique de la bourgeoisie visant à présenter le Yucatan comme une société mestiza. Au début du XXe siècle, cette région du Mexique comptait des gentes de vestido habillés à l’européenne et des mestizos arborant en principe le costume yucatèque distinctif De nos jours, la diversité des huipiles portés en milieu rural révèle la coexistence de codes culturels alternatifs dans les communautés mayas.